THE SILENT SUSPECT - Pattison, Nell (London : AVON, a division of HarperCollins Publishers Ltd, 2021)
"A FIRE. A MURDER. A SILENT SUSPECT... On a quiet street, one house is burning to the ground...By the time sign language interpreter Paige Northwood arrives, flames have engulfed her client's home. Though Lukas is safe, his wife is still inside. But she was dead before the fire started... Lukas signs to Paige that he knows who killed his wife. But then he goes silent - even when the police charge him with murder. Is he guilty, or afraid? Only Paige can help him now..." --
Keywords: Northwood, Paige -- (Fictitious character) -- Fiction; Deaf -- Fiction; Murder -- Investigation -- England -- Scunthorpe -- Fiction; Scunthorpe (England) -- Fiction; Thrillers (Fiction); Detective and mystery fiction